Socioeconomic Impact of Sports Tourism on Community Health Development in Kwara State, Nigeria - Sadiq, Suleiman Sabonkudi; Uthman, Kamalud-Deen Adekunle (Applied Psychology Review, 2024)
Sports, as a major global contributor to socioeconomic development of the society, has not been explored extensively. Therefore, the current study investigated the impact of sports tourism on the social, economic, and ecological development among the people of Kwara state, Nigeria. The study examined whether sports tourism would have a significant impact on the economic, social, and ecological development of people in Kwara state. Data was collected from a sample of 117 sportsmen and women employing a descriptive survey approach. The study probed into the multifaceted effects of sports tourism utilizing a meticulously designed questionnaire. Findings revealed that economic (c2=130.23), social (c2=159.50), and ecological development (c2=150.90) with p-values < 0.05 alpha value. The study concluded that sports tourism has a significant impact on the economic, social, and ecological development of people in Kwara state. Moreover, the study also suggested that sports tourism should be encouraged since it serves as a seasonal economic advancement for small- and large-scale business. Sports tourism is also helpful to address the social challenges that afflict rural communities thus supporting community health development.